Pengaruh Perubahan Iklim terhadap Pendapatan Peternak Ayam Ras Petelur - Nita Adillah Pratiwi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
This study aims to determine the impact of climate change on the opinions of purebred chicken farmers in Maritengngae District, Sidrap Regency. Analyze the data used by calculating the total cost of production, revenue and receipts. The results of the study obtained total fixed costs by only calculating depreciation costs of Rp. 5,333 and total variable costs of Rp. 93,260,000. While income with a scale of 1,500 heads amounted to Rp.481,417,000. The impact of climate change results in heat stress in chickens, causing a decrease in egg production and egg weight. Farmer revenue on a scale of 1,500 chickens after deduction of total production costs and income Rp. 388,128,235.